Effect of by-product fusel oil-diesel blends fuel on emissions of single-cylinder CI engine - Awad, Omar Ibraheem; Kamil, Mohammed; Abed, Adnan Ajam; Jamal, Omar; Mohammed, Omar Khalaf; Mohammed, M. N.; Alobaida, Ahmed; Suwaed, Mahmood Sh.; Muhammad Yusri, Ismail; Hasan, Mohammed M. (Frontiers Media SA, 2024)
Alcohol-based fuels have gained more interest due to their production process and availability and environmental point of view so based alcohol-based fuel like fusel oil has been studied as an alternative fuel for compression ignition engine engines. The objective of this experimental study was to investigate the performance of a compression ignition engine based on a performance and emissions of cylinder single-cylinder diesel engine. To maintain the original fuel system of the engine, a fixed blending ratio of 20% v/v was used. The research findings indicated a decrease in nitrogen oxide (NO) emissions when using fusel oil–diesel (F20) compared to diesel. Still, higher fuel consumption was observed due to the lower energy content of fusel oil. However, F20 led to increased carbon monoxide (CO) emissions and hydrocarbons (HC) compared to diesel. The most significant reduction in NOx emissions by up to 20% occurred at an engine speed of 1,500 rpm and an engine load of 75%, possibly attributed to the higher water content in fusel oil. It is crucial to evaluate the trade-offs between these parameters carefully. Insight into these trade-offs may facilitate the optimization of fusel oil use as a prospective fuel alternative for internal combustion engines.